TEACHING AND LEARNING PROCESS OF SPEAKING - Susanty, Henny; Ritonga, Dewi; Tursina, Puan (STKIP Bina Bangsa Getsempena Banda Aceh, 2017)
This study was investigated the process of language teaching and learning of speakingÂ in terms ofÂ teaching materials, teaching methods and learning assessments to the studentsâ at MTsN Blangpidie in the Academic years of Â 2016/2017. This studyÂ was a descriptiveÂ research. Two English teachers who taught at MTsN Blangpidie were participated in this study. An Interview was used to collect the data. The data were recorded, transcribed and coded based on the the problems. The finding of the study showedÂ that the teachers at MTsN Blangpidie ofÂ South West Aceh used various teaching materials, teaching strategies and also learning assessments.Â Keywords: Speaking, Teaching Materials, Teaching Methods and Learning Assessments